Gary J. Bass, The Blood Telegram: India’s Secret War in East Pakistan - Mr. Khusrow Akkas Abbasi (CISS Insight Journal, 2014)
The Blood Telegram: India’s Secret War in East Pakistan by Gary J. Bass provides a historical look into events surrounding the creation of Bangladesh. The book provides us an insight into how Cold War geopolitics influenced the course of war and also talks about the direct role of the US in India-Pakistan war of 1971. It has been published in India as well as in the US, though, under a different sub-title. Bass is also the author of The Origins of Humanitarian Intervention and Stay the Hand of Vengeance: The Politics of War Crimes Tribunals. The author is presently a professor of politics and international affairs at Princeton University. He is a former reporter of The Economist and has also written for The New York Times, The New Yorker, The Washington Post, and other newspapers, besides Foreign Affairs, and Foreign Policy. Blood Telegram is a detailed description of events leading to India-Pakistan war of 1971 and the creation of Bangladesh. The author has done extensive research by looking into primary sources, declassified documents of the US State Department and tapes of conservations of Richard Nixon and Henry Kissinger, and has interviewed American and Indian eyewitnesses of the events. The book details atrocities committed against the civilian population during the war and how Nixon and Kissinger aided and abetted in what the author calls “genocide”.